Calcium carbonate composite modifier and modification method
The compact coating of calcium carbonate is formed through the composite modifier of stearic acid, polyethylene glycol, aluminate, zirconate, n-butanol and triethanolamine, and the phase caused by its surface hydrophilic and oleophobic properties is solved. The poor capacitance problem improves compatibility and dispersion with polymer materials and expands its application scope.
Patent Information
- Application Number
- CN202411440754.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-16
- Publication Date
- 2025-01-17
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
The hydrophilic and oleophobic properties of calcium carbonate surface lead to poor compatibility with polymer materials and easy agglomeration, affecting the mechanical properties of composite materials.
Using composite modifiers of stearic acid, polyethylene glycol, aluminate, zirconate, n-butanol and triethanolamine, a tight coating is formed through chemical reactions and multi-point adsorption, thereby improving the oleophilic and hydrophobic calcium carbonate. Characteristics and dispersion.
It significantly improves the compatibility and dispersion of calcium carbonate with polymer materials, enhances the overall performance of composite materials, and expands its application scope to plastics, coatings, papermaking, rubber and other fields.
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of calcium carbonate modification, and particularly relates to a calcium carbonate composite modifier and a modification method. Background Art
[0002] As an important functional inorganic filler, calcium carbonate is widely used in industrial fields such as plastics, rubber, coatings and papermaking. However, due to its hydrophilic and oleophobic surface and easy aggregation, calcium carbonate has poor compatibility with polymer materials, which can easily cause poor interfacial bonding, resulting in a decrease in the overall mechanical properties of the composite material. An effective way to solve this problem is to modify the surface of calcium carbonate.
[0003] Surface treatment of calcium carbonate powder has injected new vitality into the application of calcium carbonate. Surface-treated calcium carbonate has a wide range of applications and more perfect performance, making the surface treatment of calcium carbonate a hot topic in the industry. The current surface modification methods of calcium carbonate often use various coupling agents, fatty acids and their salts, surfactants, etc. for modification. The compatibility of modified calcium carbonate in polymers is greatly improved, but because these modifiers are small molecular compounds, the inert organic groups are relatively small, and the intermolecular forces between them and the organic polymer system are relatively weak, which may lead to weak interaction between calcium carbonate powder and the organic polymer system, making the effect of calcium carbonate powder in enhancing polymer materials limited. Therefore, it is of great significance to research and develop new and efficient calcium carbonate activators. Summary of the invention
[0004] In order to overcome the above-mentioned deficiencies of the prior art, the present invention provides a composite modifier for activating the surface of calcium carbonate. Through the synergistic effect of stearic acid, polyethylene glycol, aluminate, zirconate, n-butanol and triethanolamine, the modified calcium carbonate has excellent lipophilic and hydrophobic properties, thereby making it have broad application prospects in the fields of plastics, coatings, papermaking, rubber and artificial stone slabs.
[0005] In order to achieve the above object, the technical solution adopted by the present invention is:
[0006] The first aspect of the present invention provides a calcium carbonate composite modifier, which contains stearic acid, polyethylene glycol, aluminate, zirconate, n-butanol and triethanolamine.
[0007] Preferably, the calcium carbonate composite modifier comprises, by mass fraction, 50%-70% of stearic acid, 5%-15% of polyethylene glycol, 5%-15% of aluminate, 5%-15% of zirconate, 2%-10% of n-butanol, and 5%-10% of triethanolamine.
[0008] Among them, aluminate and zirconate are coupling agents, which have excellent surface activity and dispersibility, can react chemically with the surface of calcium carbonate particles, reduce the interaction force between particles, improve dispersibility and processing performance, and enhance the compatibility of calcium carbonate with organic polymer materials; stearic acid alone is not ideal for treating calcium carbonate, and the cost is high, but it can achieve good synergistic effect when used in combination with a coupling agent, and basically does not affect the coupling effect of the coupling agent, and can reduce the amount of coupling agent and reduce production costs. At the same time, aluminate, zirconate and coupling agent are reasonably compounded, and the characteristics of zirconate and aluminate coupling agents are combined. It not only has a double central atom, but also has a low-carbon chain alkoxy and a long-carbon chain alkanoic acid oxy group, thereby increasing the interaction points with inorganic and organic substances. There is also a certain affinity between the double metal central atoms. The monomolecular adsorption layer formed by the composite coupling system of the two on the surface of the filler is denser than that of the single metal central atom coupling agent, showing a good synergistic effect. Polyethylene glycol and n-butanol have multiple polar groups, which can bind to multiple sites on the surface of calcium carbonate to achieve firm adsorption. This multi-point adsorption method makes the coverage of surfactant molecules on the surface of calcium carbonate more stable and not easy to desorb. Triethanolamine can be adsorbed on the surface of calcium carbonate particles, and through the steric hindrance effect and electrostatic repulsion, the calcium carbonate particles are dispersed more evenly in the medium, preventing particle agglomeration, thereby improving the dispersion stability of calcium carbonate in the system. At the same time, it can also improve the compatibility between calcium carbonate and other organic materials to a certain extent.
[0009] Preferably, the molecular weight of the polyethylene glycol is 200 to 300. Polyethylene glycol of this size has good water solubility and permeability, and can be well dispersed and volatilized on the surface of calcium carbonate, thereby improving the dispersibility of calcium carbonate in the organic phase.
[0010] The second aspect of the present invention provides a method for preparing the calcium carbonate composite modifier described in the first aspect, specifically: mixing stearic acid, polyethylene glycol, aluminate, zirconate, n-butanol, and triethanolamine, then stirring the fuel at 80°C-90°C for 0.5h-1h, and then naturally cooling to room temperature to obtain the composite modifier.
[0011] The third aspect of the present invention provides a method for modifying calcium carbonate, which comprises: first adding water to the calcium carbonate powder, heating and stirring to form a paste, then adding the calcium carbonate composite modifier described in the first aspect, and continuing to stir until a tight coating layer is formed on the surface of the calcium carbonate.
[0012] By adsorbing the modifier on the surface of calcium carbonate particles, a water-in-oil type coating layer is formed. By controlling the composition of the microemulsion, reaction conditions and other factors, the particle size and morphology of calcium carbonate can be better controlled; the coating of surfactants can improve the surface properties of calcium carbonate and enhance its dispersibility and compatibility in organic media. By inserting alcohol solvents between the modifier molecules, the order of the modifiers on the water-oil interface is more orderly, the interface film is more stable, and the interfacial tension can be further reduced, so that the activation index of the modified calcium carbonate can reach 100%.
[0013] Preferably, an equal amount of water is added to the calcium carbonate powder.
[0014] Preferably, based on the amount of calcium carbonate used, the amount of calcium carbonate composite modifier added is 16%-23%.
[0015] Preferably, the heating temperature is 90°C-95°C.
[0016] Preferably, the stirring time is continued for 60-90 minutes.
[0017] Preferably, the calcium carbonate includes light calcium carbonate, heavy calcium carbonate and a mixture thereof.
[0018] Finally, the present invention also provides modified calcium carbonate obtained by the above modification method. The modified calcium carbonate obtained by the above modification method can transform the hydrophilic and oleophobic surface into an oleophilic and hydrophobic surface, thereby solving the problem that calcium carbonate is easy to agglomerate and difficult to be evenly dispersed in polymer materials, and making its application field more extensive.
[0019] The modified calcium carbonate prepared by the method of the present invention is used in industries such as plastics, rubber, papermaking, coatings, paints, printing, cables, leather making, medicine or food, and can effectively improve the dispersibility, compatibility, stability and other properties of various materials.
[0020] The amount of modified heavy calcium carbonate prepared by the method of the present invention in the plastic, rubber, papermaking, coating, paint, printing, cable, leather, medicine or food industries can be reasonably determined according to actual needs, and the present invention does not impose any special restrictions on this.
[0021] Compared with the prior art, the present invention has the following beneficial effects:
[0022] The surface of calcium carbonate is hydrophilic and oleophobic, which makes it difficult to disperse well in polymer materials. Especially when the particle size of calcium carbonate is reduced, the performance of the composite material filled with calcium carbonate is further reduced due to the agglomeration of calcium carbonate, and it is even unusable. Therefore, it is very necessary to modify the surface of calcium carbonate. To this end, the present invention discloses a composite modifier for activating the surface of calcium carbonate. The composite modifier adopts a compounding strategy of stearic acid-coupling agent-polyol-organic amine, and is compounded by stearic acid, polyethylene glycol, aluminate, zirconate, n-butanol and triethanolamine. The composite modifier is used to modify calcium carbonate, and calcium carbonate can be mixed with the modifier to react so that the composite modifier is firmly coated on the surface of calcium carbonate. During the coating process, stearic acid acts on the alkaline groups on the surface of calcium carbonate to form a solid inner coating layer, and then further infiltration of other co-surfactants makes the interface film more stable. The composite modifier provided by the present invention can effectively improve the surface activity of calcium carbonate filler particles, so that the activation index of calcium carbonate can be as high as 100%. Therefore, the calcium carbonate modified by the composite modifier of the present invention has excellent lipophilic and hydrophobic properties. When the activated calcium carbonate is mixed with a polymer material, the compatibility of the calcium carbonate filler and the polymer material can be improved, thereby improving the overall performance of the composite material. It can be seen that the calcium carbonate modified by the composite modifier of the present invention has a wide range of application prospects in the fields of plastics, coatings, papermaking, rubber and artificial stone slabs. DETAILED DESCRIPTION
[0023] The specific embodiments of the present invention are further described below. It should be noted that the description of these embodiments is used to help understand the present invention, but does not constitute a limitation of the present invention. In addition, the technical features involved in each embodiment of the present invention described below can be combined with each other as long as they do not conflict with each other.
[0024] The experimental methods in the following examples are conventional methods unless otherwise specified, and the experimental materials used in the following examples are commercially available unless otherwise specified.
[0025] Example 1: A calcium carbonate composite modifier and modification method
[0026] (1) Preparation of a composite modifier: The composite modifier includes, by mass fraction, 50% of stearic acid, 15% of polyethylene glycol (molecular weight of 200), 10% of aluminate, 10% of zirconate, 5% of n-butanol, and 10% of triethanolamine; the components are weighed according to the above proportions, mixed, stirred at 85° C. for 1 h, and then naturally cooled to room temperature to obtain the composite modifier.
[0027] (2) Weigh 100 g of calcium carbonate (light calcium carbonate) and add it to a 500 mL three-necked flask. Then add 100 mL of deionized water, heat to 90°C in an oil bath, and stir (350 r / min) until it becomes a paste.
[0028] (3) Based on the amount of calcium carbonate, add 20% (mass fraction) of the composite modifier, continue stirring in a 90°C oil bath for 90 minutes, and stop stirring after naturally cooling to room temperature;
[0029] (4) The mixture in the flask reactor is taken out, filtered, dried at 70° C. for 72 h, and then crushed to obtain modified calcium carbonate powder.
[0030] Example 2: A calcium carbonate composite modifier and modification method
[0031] (1) Preparation of a composite modifier: The composite modifier includes, by mass fraction, 60% of stearic acid, 10% of polyethylene glycol, 5% of aluminate, 15% of zirconate, 2% of n-butanol, and 8% of triethanolamine; the components are weighed according to the above proportions, mixed, stirred at 85° C. for 1 h, and then naturally cooled to room temperature to obtain the composite modifier.
[0032] (2) Weigh 100 g of calcium carbonate and add it to a 500 mL three-necked flask. Then add 100 mL of deionized water, heat to 90°C in an oil bath, and stir until it becomes a paste.
[0033] (3) Based on the amount of calcium carbonate, add 20% (mass fraction) of the composite modifier, continue stirring in a 90°C oil bath for 90 minutes, and stop stirring after naturally cooling to room temperature;
[0034] (4) The mixture in the flask reactor is taken out, filtered, dried at 70° C. for 72 h, and then crushed to obtain modified calcium carbonate powder.
[0035] Example 3: A calcium carbonate composite modifier and modification method
[0036] (1) Preparation of a composite modifier: The composite modifier includes, by mass, 70% of stearic acid, 5% of polyethylene glycol, 5% of aluminate, 10% of zirconate, 5% of n-butanol, and 5% of triethanolamine; the components are weighed according to the above proportions, mixed, stirred at 85° C. for 1 h, and then naturally cooled to room temperature to obtain the composite modifier.
[0037] (2) Weigh 100 g of calcium carbonate and add it to a 500 mL three-necked flask. Then add 100 mL of deionized water, heat to 90°C in an oil bath, and stir until it becomes a paste.
[0038] (3) Based on the amount of calcium carbonate, add 20% (mass fraction) of the composite modifier, continue stirring in a 90°C oil bath for 90 minutes, and stop stirring after naturally cooling to room temperature;
[0039] (4) The mixture in the flask reactor is taken out, filtered, dried at 70° C. for 72 h, and then crushed to obtain modified calcium carbonate powder.
[0040] Example 4: A calcium carbonate composite modifier and modification method
[0041] (1) Preparation of a composite modifier: The composite modifier includes, by mass fraction, 50% of stearic acid, 5% of polyethylene glycol, 15% of aluminate, 15% of zirconate, 7% of n-butanol, and 8% of triethanolamine; the components are weighed according to the above proportions, mixed, stirred at 85° C. for 1 h, and then naturally cooled to room temperature to obtain the composite modifier.
[0042] (2) Weigh 100 g of calcium carbonate and add it to a 500 mL three-necked flask. Then add 100 mL of deionized water, heat to 90°C in an oil bath, and stir until it becomes a paste.
[0043] (3) Based on the amount of calcium carbonate, add 20% (mass fraction) of the composite modifier, continue stirring in a 90°C oil bath for 90 minutes, and stop stirring after naturally cooling to room temperature;
[0044] (4) The mixture in the flask reactor is taken out, filtered, dried at 70° C. for 72 h, and then crushed to obtain modified calcium carbonate powder.
[0045] Example 5: A calcium carbonate composite modifier and modification method
[0046] (1) Preparation of a composite modifier: The composite modifier includes, by mass fraction, 60% of stearic acid, 10% of polyethylene glycol, 8% of aluminate, 8% of zirconate, 7% of n-butanol, and 7% of triethanolamine; the components are weighed according to the above proportions, mixed, stirred at 85° C. for 1 h, and then naturally cooled to room temperature to obtain the composite modifier.
[0047] (2) Weigh 100 g of calcium carbonate and add it to a 500 mL three-necked flask. Then add 100 mL of deionized water, heat to 90°C in an oil bath, and stir until it becomes a paste.
[0048] (3) Based on the amount of calcium carbonate, add 20% (mass fraction) of the composite modifier, continue stirring in a 90°C oil bath for 90 minutes, and stop stirring after naturally cooling to room temperature;
[0049] (4) The mixture in the flask reactor is taken out, filtered, dried at 70° C. for 72 h, and then crushed to obtain modified calcium carbonate powder.
[0050] Example 6: A calcium carbonate composite modifier and modification method
[0051] (1) Preparation of a composite modifier: The composite modifier includes, by mass fraction, 70% of stearic acid, 6% of polyethylene glycol, 7% of aluminate, 7% of zirconate, 5% of n-butanol, and 5% of triethanolamine; the components are weighed according to the above proportions, mixed, stirred at 85° C. for 1 hour, and then naturally cooled to room temperature to obtain the composite modifier.
[0052] (2) Weigh 100 g of calcium carbonate and add it to a 500 mL three-necked flask. Then add 100 mL of deionized water, heat to 90°C in an oil bath, and stir until it becomes a paste.
[0053] (3) Based on the amount of calcium carbonate, add 20% (mass fraction) of the composite modifier, continue stirring in a 90°C oil bath for 90 minutes, and stop stirring after naturally cooling to room temperature;
[0054] (4) The mixture in the flask reactor is taken out, filtered, dried at 70° C. for 72 h, and then crushed to obtain modified calcium carbonate powder.
[0055] Comparative Example 1: A calcium carbonate composite modifier and modification method
[0056] (1) Preparation of a composite modifier: The composite modifier includes, by mass fraction, 50% of stearic acid, 15% of polyethylene glycol, 15% of aluminate, 10% of n-butanol, and 10% of triethanolamine; the components are weighed according to the above proportions, mixed, stirred at 85° C. for 1 hour, and then naturally cooled to room temperature to obtain the composite modifier.
[0057] (2) Weigh 100 g of calcium carbonate and add it to a 500 mL three-necked flask. Then add 100 mL of deionized water, heat to 90°C in an oil bath, and stir until it becomes a paste.
[0058] (3) Based on the amount of calcium carbonate, add 20% (mass fraction) of the composite modifier, continue stirring in a 90°C oil bath for 90 minutes, and stop stirring after naturally cooling to room temperature;
[0059] (4) The mixture in the flask reactor is taken out, filtered, dried at 70° C. for 72 h, and then crushed to obtain modified calcium carbonate powder.
[0060] Comparative Example 2: A calcium carbonate composite modifier and modification method
[0061] (1) Preparation of a composite modifier: The composite modifier includes, by mass fraction, 50% of stearic acid, 15% of polyethylene glycol, 15% of zirconate, 10% of n-butanol, and 10% of triethanolamine; the components are weighed according to the above proportions, mixed, stirred at 85° C. for 1 hour, and then naturally cooled to room temperature to obtain the composite modifier.
[0062] (2) Weigh 100 g of calcium carbonate and add it to a 500 mL three-necked flask. Then add 100 mL of deionized water, heat to 90°C in an oil bath, and stir until it becomes a paste.
[0063] (3) Based on the amount of calcium carbonate, add 20% (mass fraction) of the composite modifier, continue stirring in an oil bath for 90 minutes, and stop stirring after naturally cooling to room temperature;
[0064] (4) The mixture in the flask reactor is taken out, filtered, dried at 70° C. for 72 h, and then crushed to obtain modified calcium carbonate powder.
[0065] The modified calcium carbonate prepared in Examples 1-6 and Comparative Examples 1-2 was subjected to performance tests (activation degree and contact angle). The activation degree test method is as follows: 5 g of modified calcium carbonate is weighed with an electronic balance, distilled water is added, ultrasonic oscillation is performed for 15 minutes, and then the sample of the floating part is taken out and dried, and the sample is weighed and recorded with an analytical balance. The activation rate is H = weight of the floating part in the sample / total weight of the sample. The contact angle measurement method is as follows: the modified calcium carbonate powder is pressed into tablets (tablet pressing conditions: pressure is 20 MPa, and the pressure holding time is 4 min), and the contact angle of the liquid on the surface of the modified calcium carbonate tablet is measured at room temperature using an OCA40 video contact angle meter. The above test results are shown in Table 1.
[0066] As can be seen from the performance test results (Table 1) of the calcium carbonate of the embodiment and the comparative example and the unmodified calcium carbonate, the embodiment 1-6 obtains a kind of calcium carbonate composite modifier by the composite of stearic acid-coupling agent-polyol-organic amine, and then modifies the calcium carbonate by the microemulsion wet modification process. The composite modifier of this stearic acid-coupling agent-polyol-organic amine can form a coating layer on the surface of calcium carbonate particles, reduce the agglomeration phenomenon between particles, and improve the dispersibility of calcium carbonate in the matrix. Wherein, the coupling agent (aluminate, zirconate) can form a chemical bond between calcium carbonate and the organic matrix, improve the interfacial compatibility between the two, and enhance the interfacial bonding force. Stearic acid can further improve the stability of interfacial bonding through the interaction of lipophilic long-chain alkyl and organic matrix. The polar group of the alcohol solvent can be combined with multiple sites on the surface of calcium carbonate, thereby realizing firm adsorption, making the covering of surfactant molecules on the surface of calcium carbonate more stable, not easy for desorption. Organic amines can be adsorbed on the surface of calcium carbonate particles, and through steric hindrance effect and electrostatic repulsion, calcium carbonate particles are dispersed more evenly in the medium, preventing particles from agglomerating, thereby improving the dispersion stability of calcium carbonate in the system. Simultaneously, it can also improve the compatibility between calcium carbonate and other organic materials to a certain extent. Therefore, the composite of stearic acid-coupling agent-polyol-organic amine in embodiment 1-6 can further promote the surface activity of calcium carbonate, so that its surface is converted from hydrophilic to hydrophobic. In addition, adding triethanolamine can regulate the fluidity and flexibility of the interfacial film, reduce interfacial tension, and by inserting between surfactant molecules, the order of surfactant on the interface is more orderly, and the interfacial film is more stable, thereby improving its dispersibility, enhancing its compatibility with matrix, and improving the performance stability of composite material.
[0067] Table 1 Performance of modified calcium carbonate prepared by different ratio methods
[0068]
[0069] In summary, the composite modifier of the present invention is used to modify the surface of calcium carbonate, and a tight coating layer can be formed on the surface of calcium carbonate, and the hydrophilic and oleophobic surface is converted into an oleophilic and hydrophobic surface, thereby solving the problem that calcium carbonate is easy to agglomerate and difficult to be uniformly dispersed in polymer materials. At the same time, the formed coating layer interface film is stable, and the activation rate can be as high as 100%. Therefore, the calcium carbonate modified by the composite modifier of the present invention has excellent oleophilic and hydrophobic properties, and has a wide range of application prospects in the fields of plastics, coatings, papermaking, rubber and artificial stone slabs.
[0070] The embodiments of the present invention are described in detail above, but the present invention is not limited to the described embodiments. For those skilled in the art, various changes, modifications, substitutions and variations of these embodiments are made without departing from the principles and spirit of the present invention, and still fall within the protection scope of the present invention.
Claims
1. A calcium carbonate composite modifier, characterized in that: The calcium carbonate composite modifier contains stearic acid, polyethylene glycol, aluminate, zirconate, n-butanol and triethanolamine.
2. A calcium carbonate composite modifier according to claim 1, characterized in that, Calculated by mass fraction, the calcium carbonate composite modifier comprises 50%-70% of stearic acid, 5%-15% of polyethylene glycol, 5%-15% of aluminate, 5%-15% of zirconate, 2%-10% of n-butanol and 5%-10% of triethanolamine.
3. A calcium carbonate composite modifier according to claim 1 or 2, characterized in that, The molecular weight of the polyethylene glycol is 200-300.
4. The preparation method of the calcium carbonate composite modifier according to any one of claims 1 to 3, characterized in that: Mix stearic acid, polyethylene glycol, aluminate, zirconate, n-butanol and triethanolamine, then stir the fuel oil at 80℃-90℃ for 0.5h-1h, and then cool naturally to room temperature to obtain a composite modifier.
5. A method for modifying calcium carbonate, characterized in that: First, add water to the calcium carbonate powder, heat and stir to form a paste, then add the calcium carbonate composite modifier according to any one of claims 1 to 3, and continue stirring until a tight coating layer is formed on the surface of the calcium carbonate.
6. A method for modifying calcium carbonate according to claim 5, characterized in that, Add an equal amount of water to the calcium carbonate powder.
7. A method for modifying calcium carbonate according to claim 5, characterized in that: Based on the amount of calcium carbonate used, the addition amount of the calcium carbonate composite modifier is 16%-23%.
8. A method for modifying calcium carbonate according to claim 5, characterized in that: The heating temperature is 90°C-95°C.
9. A method for modifying calcium carbonate according to claim 5, characterized in that, The stirring time is continued for 60-90 minutes.
10. A method for modifying calcium carbonate according to claim 5, characterized in that: The calcium carbonate includes light calcium carbonate, heavy calcium carbonate and a mixture thereof.
Citation Information
Patent Citations
Enhanced type composite filler and method for preparing fiber-reinforced plastic product by using same
CN102558610A
Calcium carbonate surface-active agent
CN103432958A
Method for modifying heavy calcium carbonate by palm oil
CN104164098A
Filler surface treatment agent for underwater use
JP1994126144A
Process for the Surface Modification of Particles
US20110048923A1